Vertical intertidal variation of organic matter stocks and patterns of sediment deposition in a mesotidal coastal wetland. (5th August 2022) - de los Santos, Carmen B.; Lahuna, François; Silva, André; Freitas, Cátia; Martins, Márcio; Carrasco, A. Rita; Santos, Rui
Abstract: Tidal coastal wetlands, common home to seagrass and salt marshes, are relevant carbon sinks due to their high capacity to accumulate and store organic carbon in their sediments. Recent studies demonstrated that the spatial variability of this organic carbon within the same wetland system can be significant. Some of the environmental drivers of this spatial variability remain understudied and the selection of the most relevant ones can be context dependent. Here we investigated the role of bed elevation, hydrodynamics, and habitat type (salt marsh and seagrass) on the organic matter (OM) net deposition-resuspension rate and superficial sedimentary stocks (top 5 cm) at the tidal wetlands of the Ria Formosa, a mesotidal coastal lagoon in South Portugal. Results showed that two vectors of spatial variation need to be considered to describe the intertidal sedimentary OM stocks: the bed elevation that imposes a decrease of the hydroperiod and thus the change of habitat from the lower seagrass Z. noltei to the upper saltmarsh S. maritimus, and the horizontal spatial variation along the secondary channels of the lagoon that imposes a decrease in the current flow velocity magnitude. The multiple linear regression analyses, using data from 40 sampling points, explained 59% of the variation of the superficial sedimentary stocks of OM in salt marshes and seagrasses of the Ria Formosa lagoon and revealed that stocks generally decrease with elevation, yet with variation among sites and habitats. It was also found that the decrease of the OM net deposition-resuspension rate with bed elevation was exponential. Our study emphasizes the importance of considering multiple environmental drivers and spatial variation for regional estimations of organic matter (and organic carbon) sedimentary stocks in coastal wetlands. Graphical abstract: Image 1 Highlights: Organic matter (OM) intertidal sedimentary stocks vary vertically and horizontally. Elevation and flow velocity explain a high variability in the OM sedimentary stock. Net deposition-resuspension rate decreases exponentially with elevation.